Ketika Diskusi Hanya di Permukaan: Analisis Gaya Diskusi "Small Talk" dan Dampaknya terhadap Kedalaman Pemahaman Konseptual Mahasiswa - Putra, Elvan; Fitri, Laila; Desrina, Ilhamni (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the "small talk" discussion style among university students and its impact on the depth of conceptual understanding. This qualitative research employed a phenomenological approach with data collected through participatory observation, in-depth interviews, and document analysis of discussion transcripts from two different courses. The subjects were 25 students from various study programs who actively participated in classroom discussions. The findings indicate that "small talk" discussions—characterized by superficial responses, avoidance of critical debate, repetition of opinions without elaboration, and reliance on personal anecdotes—tend to hinder the development of deeper conceptual understanding. This style often arises due to low self-confidence, fear of being wrong, lack of preparation, and a classroom culture that does not encourage critical inquiry. While "small talk" can create a comfortable atmosphere, it limits cognitive engagement and reduces opportunities for analytical and evaluative thinking. This study suggests the need for more structured and guided discussion strategies to encourage deeper intellectual engagement.